Resilience to Climate Change-Induced Challenges in the Mekong River Basin : The Role of the MRC - Schmeier, Susanne (World Bank, Washington, DC, 2014)
Climate change and its consequences, ranging from increased water variability to more extreme weather events and from sea level rise to ecosystem changes, introduce new challenges to transboundary watercourses, which already face a variety of collective action problems due to their border-crossing nature. Other changes occurring in river basins, such as changing water-use patterns, development of large infrastructure schemes, and changing socioeconomic development levels of riparian states also challenge the institutional capacity of current cooperative management mechanisms. Thus, River Basin Organizations (RBOs), which manage the river basins, must be highly adaptive to ensure not only resilience to change but also long-term sustainable development of the basin and its people. This paper examines the 'adaptation capacity' of the Mekong River Commission (MRC), which manages the Mekong River Basin, a river basin particularly vulnerable to challenges related to climate change as well as to human-caused change. Resilience may be encoded in treaty provisions, but in practice it depends on a broad array of factors, most importantly the capacity of the major institution established by the riparian states to cooperatively manage the river basin. Several key points have been identified regarding the contribution of the MRC to increasing resilience to environmental and human-caused change in the Mekong River Basin. The aim of the paper is to assess the adaptation capacity of a particular RBO, the MRC, and the related resilience of the Mekong River Basin with regard to climate change but including other challenges such as hydropower development and the related change induced in the basin. This assessment is based on an analytical framework developed with the overall aim to provide a means for assessing the adaptation capacity of RBOs and thus apply it to other river basins as well.